Correction: Exploring the non-communicable disease (NCD) network of multi-morbid individuals in India: A network analysis. - PLOS Global Public Health Staff (PLOS Global Public Health, 2023)
[This corrects the article DOI: 10.1371/journal.pgph.0000512.].